Development of Islamic Education Curriculum Instruments for Early Childhood through Semester Learning Plans (RPS) for Gender Responsive Islamic Courses - Evi Muafiah; Ahmad Mujib; Syaiful Arif (TADRIS: Jurnal Pendidikan Islam, 2022)
This study aims to test the feasibility of gender responsive semester learning plans (RPS) according to gender responsive learning experts, learning design experts, and the effectiveness of using gender responsive RPS in Islamic Religious Colleges (PTKI). This research is developmental by using the instructional system model of Thiagarajan, Semmel and Semmel (1974) with a modified 4-D model. The 4-D model consists of Define, Design, Develop and Disseminate. In this study, modification of the 4-D model was carried out, namely simplification from four stages to three stages. The results showed that the RPS was gender responsive from the development of the 4-D model in the subjects of Al-Qur'an Studies, Hadith Studies, Introduction to Islamic Studies, and the History of Islamic Civilization are considered appropriate according to gender responsive learning experts and learning design experts. The limited trial showed a very satisfactory response based on the assessment of observer lecturers and PIAUD students who had participated in this study.